THE INVOLVEMENT OF ENGLISH TEACHERS ON MINIMUM COMPETENCY ASSESSMENT (AKM) - Prativi Khilyatul Auliya (Universitas Muhammadiyah Metro, 2022)
Minimum Competency Assessment or AKM is one of the instruments used by the Indonesian government to evaluate the education system. Several studies have been done related to AKM. However, there are no studies about English teachers' involvement in AKM. Therefore, this study aimed at investigating English teachers' participation in AKM. It covers; (1) English teachers' perception of AKM and (2) English teachers' action plans to support students facing AKM. This is a survey study with 23 English teachers from secondary and high schools in East Java as participants. Online questionnaires and phone interviews were used as instruments to collect the data. The result shows that most English teachers have a positive perception of AKM. They show their positive emotion, motivation, and belief in AKM. Furthermore, the English teachers have created action plans as a form of their readiness to support students facing AKM. The planning covers teaching material, AKM exercise, teaching media, and teaching methods, and further investigation about those aspects is still needed.